2019
DOI: 10.1088/1752-7163/ab231d
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled carbon monoxide levels in obstructive sleep apnoea

Abstract: Background: Obstructive sleep apnoea (OSA) is characterised by chronic intermittent hypoxia, which enhances airway inflammation and oxidative stress. Exhaled carbon monoxide (eCO), a marker for oxidative stress, has been investigated in OSA. However, previous studies could be biased as they did not differentiate patients with OSA based on smoking history, a known factor influencing eCO levels. The aim of this study to investigate eCO levels in patients with OSA and non-OSA controls and compare evening to morni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Knowledge about exhaled carbon monoxide (eCO) in OSAS is more limited than FeNO. To the extent possible, eCO has been reported higher only in severe OSAS [42], it has a weak correlation with AHI [42] and it is not normalized after one-month of C-PAP [22], probably because it needs a longer period to be normalized.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge about exhaled carbon monoxide (eCO) in OSAS is more limited than FeNO. To the extent possible, eCO has been reported higher only in severe OSAS [42], it has a weak correlation with AHI [42] and it is not normalized after one-month of C-PAP [22], probably because it needs a longer period to be normalized.…”
Section: Resultsmentioning
confidence: 99%
“…It is a marker of oxidative stress. Studies have shown elevated levels of exhaled circulating CO in patients with OSA 39 . The exhaled CO content in patients with different types of OSA is demonstrated in Fig.…”
Section: Application Of Human Exhaled Breath Components In Disease Di...mentioning
confidence: 99%
“…CO can be detected in exhaled breath in a parts per million (10 −6 , ppm) range, and it is present with elevated levels in patients with inflammatory airway diseases such as asthma, cystic fibrosis (CF), obstructive sleep apnea and non-CF bronchiectasis [ 18 , 21 , 99 , 154 , 155 , 156 , 157 ]. The mean value of exhaled CO in healthy non-smoking subjects varied between 0.94 and 3.86 ppb in the 15 studies assessed in a meta-analysis [ 158 ].…”
Section: Exhaled Gaso-transmittersmentioning
confidence: 99%